2016
DOI: 10.1002/cpdd.259
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Pharmacodynamics of Prasugrel and Clopidogrel in Healthy Japanese Volunteers

Abstract: The dosing regimen of prasugrel adjusted for Japanese patients was compared with that of clopidogrel by analyzing the pharmacokinetics and pharmacodynamics in 40 healthy Japanese subjects in a randomized, single‐blind crossover study. In period 1, the subjects received either 300 mg clopidogrel or 20 mg prasugrel; after a >2‐week interval (period 2), the drug was switched. Blood samples of 36 of the 40 subjects were collected for analysis of pharmacokinetics, pharmacodynamics, and CYP2C19 genotypes. The plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
0
31
3
Order By: Relevance
“…However, prasugrel is believed to be less affected by genotypic variability [25][26][27]. Moreover, one study found no significant difference in pharmacodynamic response for prasugrel 5 or 10 mg [28], what is in disagreement with the index data. Another study revealed that prasugrel, in contrast to clopidogrel, rapidly and independently inhibited platelet aggregation of CYPC19 carriers in healthy Japanese subjects [28].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…However, prasugrel is believed to be less affected by genotypic variability [25][26][27]. Moreover, one study found no significant difference in pharmacodynamic response for prasugrel 5 or 10 mg [28], what is in disagreement with the index data. Another study revealed that prasugrel, in contrast to clopidogrel, rapidly and independently inhibited platelet aggregation of CYPC19 carriers in healthy Japanese subjects [28].…”
Section: Discussioncontrasting
confidence: 45%
“…Moreover, one study found no significant difference in pharmacodynamic response for prasugrel 5 or 10 mg [28], what is in disagreement with the index data. Another study revealed that prasugrel, in contrast to clopidogrel, rapidly and independently inhibited platelet aggregation of CYPC19 carriers in healthy Japanese subjects [28]. However, a strong impact of PM carrying the *2 genotype on platelet function after prasugrel has also been reported [29].…”
Section: Discussioncontrasting
confidence: 42%
“…Within 20 min (King et al, 2016) Within 20 min (King et al, 2016) Within 20 min (King et al, 2016) 2 h (Ungerer et al, 2011) .4 h (De Luca, 2012) .4 h (De Luca, 2012) 4-8 h (Topol, 1999;Vorchheimer et al, 1999) Half-life 10 h (Gregov et al, 1987) 10-11 h (Eikelboom et al, 2012) 24-36 h (Eikelboom et al, 2012) 20 min (Umemura and Iwaki, 2016) 30 min to 7.5 h (Umemura et al, 2016) 7-9 h (Teng and Butler, 2013) 3-5 min (Sible and Nawarskas, 2017) 5-7 h (murine) (Zheng et al, 2016) Prodrug No Yes (CYP3A5 and CYP2C19) (Yoo et al, 2009(Yoo et al, , 2010 Yes Yes…”
Section: B Adp Receptor Inhibitorsmentioning
confidence: 99%
“…In a comparison with clopidogrel in the same study, inhibition of ADP (20 μM)–induced platelet aggregation on day 28 was lower (21.7%) in the clopidogrel 300/75‐mg group. Furthermore, inhibition of ADP (20 μM)–induced platelet aggregation 4 hours after administration of prasugrel 20 mg was similar to that 4 hours after administration of clopidogrel 300 mg in healthy Japanese CYP2C19 extensive metabolizers …”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, inhibition of ADP (20 μM)-induced platelet aggregation 4 hours after administration of prasugrel 20 mg was similar to that 4 hours after administration of clopidogrel 300 mg in healthy Japanese CYP2C19 extensive metabolizers. 25 The active metabolite of prasugrel, R-138727, has irreversible effects on P2Y 12 on the platelet membrane. 26 However, the life of circulating human platelets is only 8-10 days, and about 20% are replaced daily with new platelets.…”
Section: Discussionmentioning
confidence: 99%